Structure, function, and genetics of lipoprotein (a) - Schmidt, Konrad (J Lipid Res, 2016)
Lipoprotein (a) [Lp(a)] has attracted the interest of researchers and physicians due to its intriguing properties, including an intragenic multiallelic copy number variation in the LPA gene and the strong association with coronary heart disease (CHD). This review summarizes present knowledge of the structure, function, and genetics of Lp(a) with emphasis on the molecular and population genetics of the Lp(a)/LPA trait, as well as aspects of genetic epidemiology. It highlights the role of genetics in establishing Lp(a) as a risk factor for CHD, but also discusses uncertainties, controversies, and lack of knowledge on several aspects of the genetic Lp(a) trait, not least its function.